Déterminants Des Montants De Consentement À Payer (CAP) Déclarés Par Les Ménages Pour Une Gestion Durable De La Forêt d’Adjamey Au SudOuest Du Bénin - Miwoto, Médard; Zannou, Afio; Biaou, Gauthier (European Scientific Journal, ESJ, 2017)
The objective of this study is to analyze the factors that explain the amounts of willingness to pay (WTP) of households for the implementation of a sustainable management program of Adjamey forest in the district of Djakotomey in South-West of Benin. Indeed, the bordering populations of this forest are frequently faced with the problem of the devastation of their crops by the hippopotamuses. These in turn undergo anthropological actions causing the continued loss of their habitat. The data were collected on 110 bordering households using a semi-structured questionnaire. Based on the two-step selection model of Heckman, this study revealed that the households participation to the program of sustainable management of this forest is influenced by factors such as: the origin and level of education of the surveyed households, the fact of having been victims of the damage caused by the hippopotamuses and the fact that the household wishes an improvement of the management of this forest. Moreover, the study shows that the total area held in the forest, the total income drawn from the activities related to the forest, the membership in a management committee and the fact that the hippopotamuses are considered as a threat constitute to the explanatory factors of the amounts of willingness to pay (WTP) declared by the households.